2002
DOI: 10.1021/jf011656u
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Effect of Saturated Acyl l-Ascorbate on the Oxidation of Linoleic Acid Encapsulated with Maltodextrin or Gum Arabic by Spray-Drying

Abstract: 6-O-Palmitoyl L-ascorbate was added to linoleic acid at various molar ratios of the ascorbate to the acid, the mixtures were emulsified with a maltodextrin or gum arabic solution, and the emulsions were spray-dried to produce microcapsules. At higher molar ratios, the oil droplets in the emulsions were smaller, and the oxidative stabilities of the encapsulated linoleic acid were higher for both the maltodextrin- and gum arabic-based microcapsules. 6-O-Capryloyl, caproyl, and lauroyl L-ascorbates, which were sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
33
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 15 publications
4
33
0
2
Order By: Relevance
“…Lipophilic antioxidants are supposed to be more effective for suppressing lipid oxidation than hydrophilic ones. 2,3) Alkyl ferulates, which should be more lipophilic than unmodified ferulic acid, have recently been utilized in the food and cosmetic industries as antioxidants and radical scavenging agents. 4,5) However, no kinetic study based on adequate rate expression has been reported for the suppressive effect of ferulic acid or alkyl ferulate on the lipid oxidation.…”
mentioning
confidence: 99%
“…Lipophilic antioxidants are supposed to be more effective for suppressing lipid oxidation than hydrophilic ones. 2,3) Alkyl ferulates, which should be more lipophilic than unmodified ferulic acid, have recently been utilized in the food and cosmetic industries as antioxidants and radical scavenging agents. 4,5) However, no kinetic study based on adequate rate expression has been reported for the suppressive effect of ferulic acid or alkyl ferulate on the lipid oxidation.…”
mentioning
confidence: 99%
“…6-O-Decanoyl l-ascorbate was synthesized by the immobilized-lipase-catalyzed condensation of decanoic and l-ascorbic acids in acetone and purified according to previous procedures (Yan et al, 1999;Watanabe et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…We also synthesized acyl ascorbates using an immobilized lipase in a batch or continuous reactor (Watanabe et al, 1999;, estimated their surfactant property (Watanabe et al, 2001, and demonstrated their antioxidative ability against an unsaturated fatty acid (Watanabe et al, 2005). Furthermore, we prepared microcapsules of linoleic acid with various saturated acyl ascorbates by spray-drying, and showed its antioxidative ability against encapsulated linoleic acid ( Watanabe et al, 2002). Therefore, lipids, such as acylglycerol containing polyunsaturated fatty acids, could be used for microencapsulation with acyl ascorbate for use in industrial applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, modification of the hydroxyl groups of ascorbic acid with long-chain fatty acids was developed to improve its liposolubility. [2][3][4] Recently, a novel ascorbic acid derivative (Ge-Vit) conjugated with hydrophobic organogermanium was also prepared to improve the level of cell penetration. 5,6 The antioxidant activity of this conjugated compound was expected to be improved by the combined effects of ascorbic acid and organogermanium because organogermaium compounds have been reported to enhance immune response, 7 which may be due to its antioxidant effects.…”
mentioning
confidence: 99%